Mannan-binding lectin-associated serine protease-1 (MASP-1) mediates immune responses against Aeromonas hydrophila in vitro and in vivo in grass carp. Issue 66 (July 2017) - Dang, Yun-Fei; Shen, Yu-Bang; Xu, Xiao-Yan; Wang, Shen-Tong; Meng, Xin-Zhan; Li, Li-Sen; Zhang, Meng; Hu, Mo-Yan; Lv, Li-Qun; Wang, Rong-Quan; Li, Jia-Le
Abstract: The mannan-binding lectin-associated serine protease-1 ( MASP-1 ) gene is a crucial component of the lectin pathway in the complement and coagulation cascade. Although MASP-1 has been found in the immune system of teleosts, its immune functions in response to bacterial infection are unclear. In this study, we identified a MASP-1 homolog ( gcMASP-1 ) in the grass carp ( Ctenopharyngodon idella ). The full-length 3308-bp gcMASP-1 cDNA includes a 2160-bp open reading frame encoding a protein composed of 719 amino acids with epidermal growth factor-like, complement control protein, and trypsin-like domains. gcMASP-1 shares a high similarity with MASP-1 counterparts in other species, and it is most closely related to Cyprinus carpio MASP-1 and Sinocyclocheilus anshuiensis MASP-1. Transcription of gcMASP-1 was widely distributed in different tissues and induced by Aeromonas hydrophila in vivo and in vitro . Expression of gcMASP-1 was also affected by lipopolysaccharide and flagellin stimulation in vitro . In cells over-expressing gcMASP-1, transcript levels of almost all components, except gcMBL and gcC5, were significantly enhanced, and gcIL1β, gcTNF-α, gcIFN, gcCD59, gcC5aR1, and gcITGβ-2 were significantly upregulated after exposure to A. hydrophila ; gcMASP-1 interference downregulated the transcript levels after A. hydrophila challenge. In addition, gcMASP-1 activated NF-κB signaling. These findings indicate the vital role of gcMASP-1 in innate immunity in C. idella . Highlights: We identified gcMASP-1, a MASP-1 homolog, in grass carp. gcMASP-1 transcription was induced by A. hydrophila in vivo and in vitro. gcMASP-1 downregulation suppressed the immune response to A. hydrophila. gcMASP-1 over-expression activated NF-κB signaling. Our findings confirm gcMASP-1 involvement in innate immunity in grass carp.